2022
DOI: 10.3126/irjms.v7i1.50629
|View full text |Cite
|
Sign up to set email alerts
|

Employee Perspectives on Decent Work and Job Burnout: Evidence from Nepalese Manufacturing Industries

Abstract: Purpose: This study aims to explore the relationship between decent work and job burnout. Design/methodology/approach: The study employs a structured questionnaire for the survey. It takes into account three factors of job burnout and seven dimensions of decent work to determine whether there is any association between them. The sample includes 600 people from four industrial estates (including 40 manufacturing industries and 15 employees in each) in Nepal. Findings: The findings supported the idea that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Promoting decent work in the context of Nepal is a requirement of the International Labour Organization (ILO) programs. In Nepal, decent work is concerned with strengthening social interaction, expanding employment and employment rights, and giving social protection (Shrestha, 2022(Shrestha, , 2021 (2012) observed that institutions that support the implementation of labor laws are poor in Nepal. Furthermore, in a study, Kyloh (2008) argued for specific institutional reform measures in terms of implementation of the mechanism to put labor legislation into action strengthening the role of trade unions in the public labor inspection system to monitor compliance with labor laws at the workplace and thus to bring complaints to the Labor Court.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promoting decent work in the context of Nepal is a requirement of the International Labour Organization (ILO) programs. In Nepal, decent work is concerned with strengthening social interaction, expanding employment and employment rights, and giving social protection (Shrestha, 2022(Shrestha, , 2021 (2012) observed that institutions that support the implementation of labor laws are poor in Nepal. Furthermore, in a study, Kyloh (2008) argued for specific institutional reform measures in terms of implementation of the mechanism to put labor legislation into action strengthening the role of trade unions in the public labor inspection system to monitor compliance with labor laws at the workplace and thus to bring complaints to the Labor Court.…”
Section: Discussionmentioning
confidence: 99%
“…Decent work appears to involve the total of everyone's working-life objectives (Pereira et al, 2019). It is concerned with generating a fair income through productive work while also providing security and social protection (Shrestha, 2022). It provides opportunities for personal growth, guarantees the fundamental rights of employees, and promotes equality of opportunity and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they might stay with the existing company provided the company can provide an alluring compensation plan for them (Shepherd & Matthews, 2000;Jardine & Amig, 2001). In addition to this, implementing the concept of decent work (Shrestha, 2021(Shrestha, , 2022(Shrestha, , and 2023 can assist in creating productive workplaces and increase employee retention. In conclusion, Nepalese BFIs need to provide timely promotion opportunities and fair compensation practices so that they can retain talented employees in their organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, organizational culture is vital for the public sector to overcome challenges and improve service quality [21]. This contributes to the success of organizational change and improves employee engagement and participation [22], while promoting decent work as a key factor in advancing overall social welfare and economic growth [23]. In an organizational culture that fosters innovation and values teamwork, communication and trust strengthen business performance and growth [24].…”
Section: Introductionmentioning
confidence: 99%